IMPLEMENTATION OF MUSIC THERAPY IN THE CONTENT OF MODERN UNIVERSITY EDUCATION IN UKRAINE - Dobrovolska Rufina (Alfred Nobel University Publisher, 2023)
The modern stage of reform and qualitative changes in modern university education in Ukraine are related to the implementation of conceptual ideas of higher education, which depends on the ability of scientific and pedagogical universities staff to professional development, readiness to implement innovative technologies, active creative actions, generation of productive original ideas in new changing and dynamic professional and life situations. From this point of view, the interest in global science and practice in solving the problems posed by the modern socio-cultural space is constantly increasing. Thus, the growing flow of information, the accelerated pace of the contradictory life of a modern member of society, and the intensity of communication ties affect the psychological health of the personality of teachers and students, their quality of life, mental balance and well-being, composure and harmony, the skills to overcome stress, support ability to work in various spheres of life and professional activity. One of the effective ways to overcome these problems in the educational space is the use of technologies that create comfortable objective and subjective conditions for emotional and psychological self-regulation, ensure the person's emotional stability, prevent the syndrome of "emotional burnout" and are an important factor in achieving success in training, development and professional activity. The purpose of the article is to solve the identified problems, which contribute to the use of music therapy in the modern university space, for which it is necessary to implement the highly qualified training of personnel in music therapy and educational projects and programs which concordant with universities programs in Europe and the USA. During the 20th and 21st centuries in Europe and the USA, music therapy began to be intensively introduced into university education to activate cognitive and intellectual activity, model a health-saving educational environment, meet the special needs of student youth in inclusive education, and create a STEAM learning environment. Tasks and methods of research: today scientists of Ukraine have systematized only certain aspects of scientific knowledge about music therapy, which is introduced into the content of modern university education in Europe and the USA. In this way, the leading international experience on the issue of involving student youth in music therapy classes at the world's leading universities has not been summarized, the system of measures for attracting education seekers to these classes has not been substantiated, and data on the specifics of the content of music therapy classes have not been systematized. Therefore, there is a need for research and comparative analysis of foreign experience of introducing music therapy into modern university education. This article is devoted to the introduction of music therapy into the content of modern university education in Ukraine. It examines the theoretical and practical aspects of using music as a means of improving the mental and emotional state of students, as well as increasing the effectiveness of the educational process. The article examines scientific studies that confirm the usefulness of music therapy for mental health and improving human cognitive functions. The author also offers specific recommendations for the introduction of music therapy into the educational process, in particular, the use of music in lectures, seminars and other forms of classes. The experience of using music therapy in universities around the world, studies that confirm its effectiveness and the feasibility of introducing such an approach to education in Ukraine are briefly analysed. Based on the results of the research, the author concluded about the need to introduce music therapy into university education in Ukraine.